1974
DOI: 10.1177/000456327401100121
|View full text |Cite
|
Sign up to set email alerts
|

A New Haemoglobin Variant Haemoglobin J Birmingham a 120 (H3) Ala → Glu

Abstract: An abnormal haemoglobin, which on paper electrophoresis has the mobility of Hb J, has been found in two brothers and, in the heterozygousstate at least, is not associated with serious clinical abnormality. The structure of this hitherto unreported haemoglobin is a 120(H3) Ala -+ Glu and it is named Haemoglobin J Birmingham.A fast moving haemoglobin whose electrophoretic mobility on paper at pH 8.6 was similar to that of HbJ, was discovered in two brothers from Bangladesh during a pilot study of abnormal haemog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1975
1975
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Hb J Meerut/Hb Birmingham is a a-globin chain derived FMH characterized by replacement of alanine by glutamate at 120 amino acid position (a 120 Ala-Glu). Blackwell et al first reported this Hb variant in two sisters from Meerut, India [4], and Kamuzora et al reported in two brothers from Bangladesh [5] Harano et al [6] and Takemura et al [7] reported this Hb variant in two unrelated Japanese families; and Yalcin et al (1994) [1] in a family from Turkey. Our study is the largest reported series of Hb J Meerut of which four patients belonged to one family.…”
Section: Discussionmentioning
confidence: 99%
“…Hb J Meerut/Hb Birmingham is a a-globin chain derived FMH characterized by replacement of alanine by glutamate at 120 amino acid position (a 120 Ala-Glu). Blackwell et al first reported this Hb variant in two sisters from Meerut, India [4], and Kamuzora et al reported in two brothers from Bangladesh [5] Harano et al [6] and Takemura et al [7] reported this Hb variant in two unrelated Japanese families; and Yalcin et al (1994) [1] in a family from Turkey. Our study is the largest reported series of Hb J Meerut of which four patients belonged to one family.…”
Section: Discussionmentioning
confidence: 99%
“…Hb J-Meerut results from a C ->A mutation (GCG->GAG) at codon 120 of the α1 or α2 globin gene, changing the alanine to glutamic acid at residue 120 of the α chain 1 , 2 , 3 . This variant was first reported in two sisters from Meerut, Utlar Pradesh, India 1 and in two brothers from Bangladesh living in Birmingham, England 2 ; subsequently the same abnormal hemoglobin, was described in one Japanese family 4 and in one Turkish family 5 . The present study provides details about α Hb J Meerut heterozygous Turkish male who is unrelated to the family with the same abnormal hemoglobin described previously from Turkey.…”
Section: Introductionmentioning
confidence: 99%